The World Atlas of Archaeology (1985)
English edition of Le Grand Atlas de l'archéologie © 1985 Encyclopaedia Universalis. 162-195: The Prehistoric/Ancient Near East; 178-179: The Invention of Writing. Contributions by Daniel Arnaud, Olivier Aurenche, Thierry Berthoud, Dominique Beyer, Serge Cleuziou, Francis Hours, Jean-Louis Huot, Jean-François Jarrige, Jean-Claude Margueron